2019
DOI: 10.3168/jds.2018-15226
|View full text |Cite
|
Sign up to set email alerts
|

Low-fat yogurt alleviates the pro-inflammatory cytokine IL-1β-induced intestinal epithelial barrier dysfunction

Abstract: Yogurt is a source of bioactive compounds and probiotic microorganisms that modify immunity and metabolism to benefit human health beyond nutrition. In this study, we examined the capacity of yogurt to prevent epithelial barrier disruption in vitro. Different preparations of yogurt were added apically to Caco-2 monolayers before IL-1β exposure. Dulbecco's modified Eagle medium containing 25% (vol/vol) low-fat yogurt prevented cytokine-induced transepithelial resistance reduction and increases to paracellular p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Some researchers reported that the administration of a combination of L. rhamnosus and L. helveticus probiotics did not prevent the development of moderate to severe gastroenteritis (Freedman et al, 2018). However, the findings of Zhai et al (2019) strongly suggest that low-fat yogurt fermented by Streptococcus thermophilus and L. bulgaricus can maintain intestinal barrier integrity. At present, it is unclear which probiotics affect the gut microbes, which makes it difficult to choose which probiotics to use to treat enteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers reported that the administration of a combination of L. rhamnosus and L. helveticus probiotics did not prevent the development of moderate to severe gastroenteritis (Freedman et al, 2018). However, the findings of Zhai et al (2019) strongly suggest that low-fat yogurt fermented by Streptococcus thermophilus and L. bulgaricus can maintain intestinal barrier integrity. At present, it is unclear which probiotics affect the gut microbes, which makes it difficult to choose which probiotics to use to treat enteritis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that overexpression of MLCK leads to increase intestinal epithelial TJ permeability [15,44]. Many studies have reported that increased MLCK activity phosphorylates MLC and subsequently leads to the centripetal contraction of the TJ complex, eventually result in the opening of the intestinal epithelial barrier [45][46][47]. The results from our study clearly indicate that LPS promoted the expression of MLCK and MLC and diminished the expression of key sealing TJ proteins, such as ZO-1, occludin, and claudin-1, causing varying degrees of displacement of the claudin-1 and ZO-1 proteins.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, targeted knockdown of MEKK-1, IKKβ, or NF-κB p65 prevented the IL-1β-induced increase in MLCK gene activity and increase in intestinal epithelial TJ permeability, confirming the regulatory role of MEKK-1, IKKβ and the NF-κB p50/p65 axis on MLCK gene activation ( 88 ). Zhai and colleagues recently showed that low-fat yogurt prevented the IL-1β-induced intestinal barrier disruption by inhibiting the upregulation of MLCK gene expression in Caco-2 cells ( 122 ). These studies also showed that the IL-1β-induced increase in NF-κB activation is inhibited by low-fat yogurt application to Caco-2 cells ( 122 ).…”
Section: Mechanisms Of the Il-1β-induced Modulation Of The Intestinal Tj Barriermentioning
confidence: 99%
“…Zhai and colleagues recently showed that low-fat yogurt prevented the IL-1β-induced intestinal barrier disruption by inhibiting the upregulation of MLCK gene expression in Caco-2 cells ( 122 ). These studies also showed that the IL-1β-induced increase in NF-κB activation is inhibited by low-fat yogurt application to Caco-2 cells ( 122 ). Collectively, these studies show that IL-1β-induced increases in MLCK gene activity and protein synthesis are required for increased intestinal TJ permeability.…”
Section: Mechanisms Of the Il-1β-induced Modulation Of The Intestinal Tj Barriermentioning
confidence: 99%